Transanal Endoscopic Microsurgery Principles and Techniques - Cataldo, Peter; Buess, Gerhard F. (Springer New York : Imprint: Springer, 2009)
Transanal Endoscopic Microsurgery: Principles and Techniques is the first book to present a complete review of an exciting developing technology. Cancer of the rectum remains a significant health problem, despite the increasing improvement of survival rates. The improvement in patient care comes from many sources: more accurate preoperative staging, aggressive neoadjuvant therapy and improved surgical techniques. Surgical extirpation continues to be the cornerstone of curative treatment of this potentially lethal disease. Transanal endoscopic microsurgery (TEM) is a technique for the performance of local excision by way of a binocular magnified operating system. Comparative trials demonstrate significantly better oncologic results for rectal cancer treated by TEM compared to conventional local excision. TEM provides a technically superior method for excision of rectal polyps and select early rectal cancers, with lower costs and fewer complications when compared to conventional approaches. The editors and chapter authors of Transanal Endoscopic Microsurgery: Principles and Techniques are the world's leading experts on TEM and their collective clinical experience is reflected in the practically oriented approach in every chapter. The text will prove to be an asset to any colorectal or general surgeon's library.